ANALISIS FAKTOR YANG MEMPENGARUHI KETERATURAN KUNJUNGAN ANTENATAL CARE DI PUSKESMAS SUGIO KABUPATEN LAMONGAN - Immaya, Nindia Dwi; Martini, Diah Eko; Ekawati, Heni; Sulistiyo, Evi Jihan; Damayanti, Dwi (Fakultas Ilmu Kesehatan Universitas Siliwangi, 2024)
Initial survey found that there are still many pregnant women who do not regularly attend Antenatal Care visits. The aim of this study is to identify the factors influencing the regularity of Antenatal Care visits among pregnant women in Sugio Community Health Center, Lamongan Regency. This research has an analytical correlation design with a cross-sectional approach. The population consists of all pregnant women who have recorded Antenatal Care visits at Sugio Community Health Center. Using the Consecutive Sampling technique, a total of 50 pregnant women were obtained as the sample for this study, and data were collected through a questionnaire. The collected data were then tabulated and analyzed using the chi-square test with a significance level of p=0.05. The results of the study showed that the majority of pregnant women, 38 (76%), attended Antenatal Care visits regularly, while a small portion, 12 (24%), did not attend Antenatal Care visits regularly. Based on the analysis, it was found that the factor of parity had a p-value of 0.007 (p0.05), indicating a relationship between the respondents’ parity and the regularity of Antenatal Care visits. The factor of knowledge level yielded a p-value of 0.000 (p0.05), indicating a relationship between knowledge level and the regularity of Antenatal Care visits. The factor of famil support obtained a p-value of 0.000 (p0.05), indicating a relationship between family support and the regularity of Antenatal Care visits. Lastly, the factor of healthcare provider support had a p-value of 0.010 (p0.05), indicating a relationship between healthcare provider support and the regularity of Antenatal Care visits. Based on the research findings, it is hoped that pregnant women will be able to attend Antenatal Care visits regularly to ensure good health for their fetus.